Acute Ethanol Increases IGF‐I‐Induced Phosphorylation of ERKs by Enhancing Recruitment of p52‐Shc to the Grb2/Shc Complex. Issue 6 (19th December 2016) - Dean, Matthew; Lassak, Adam; Wilk, Anna; Zapata, Adriana; Marrero, Luis; Molina, Patricia; Reiss, Krzysztof
Abstract : Ethanol plays a detrimental role in the development of the brain. Multiple studies have shown that ethanol inhibits insulin‐like growth factor I receptor (IGF‐IR) function. Because the IGF‐IR contributes to brain development by supporting neural growth, survival, and differentiation, we sought to determine the molecular mechanism(s) involved in ethanol's effects on this membrane‐associated tyrosine kinase. Using multiple neuronal cell types, we performed Western blot, immunoprecipitation, and GST‐pulldowns following acute (1–24 h) or chronic (3 weeks) treatment with ethanol. Surprisingly, exposure of multiple neuronal cell types to acute (up to 24 h) ethanol (50 mM) enhanced IGF‐I‐induced phosphorylation of extracellular regulated kinases (ERKs), without affecting IGF‐IR tyrosine phosphorylation itself, or Akt phosphorylation. This acute increase in ERKs phosphorylation was followed by the expected inhibition of the IGF‐IR signaling following 3‐week ethanol exposure. We then expressed a GFP‐tagged IGF‐IR construct in PC12 cells and used them to perform fluorescence recovery after photobleaching (FRAP) analysis. Using these fluorescently labeled cells, we determined that 50 mM ethanol decreased the half‐time of the IGF‐IR‐associated FRAP, which implied that cell membrane‐associated signaling events could be affected. Indeed, co‐immunoprecipitation and GST‐pulldown studies demonstrated that the acute ethanol exposure increased the recruitment of p52‐Shc to the Grb2‐Shc complex, which is known to engage the Ras‐Raf‐ERKs pathway following IGF‐1 stimulation. These experiments indicate that even a short and low‐dose exposure to ethanol may dysregulate function of the receptor, which plays a critical role in brain development. J. Cell. Physiol. 232: 1275–1286, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In the current study, we show a novel effect of ethanol on the IGF‐I receptor (IGF‐IR) signaling, and provided a possible mechanism through which this occurs. We determine that ethanol enhances mobility of the IGF‐IR molecules within the cell membrane, and that this stimulatory effect enhances formation of the Grb2‐Shc signaling complex leading to the transient increase of the signal toward extracellular regulated kinases (ERKs). Because of the critical role of the IGF‐IR signaling in neuronal growth and survival, and the detrimental effects of alcohol on CNS development, we believe that our new data will help in better understanding of the fetal alcohol syndrome.